Montelukast for postinfectious cough in adults: a double-blind randomised placebo-controlled trial. - Wang, K; Birring, S; Taylor, K; Fry, N; Hay, A; Moore, M; Jin, J; Perera, R; Farmer, A; Little, P; Harrison, T; Mant, D; et al. (2014)
BACKGROUND: Postinfectious cough is common in primary care, but has no proven effective treatments. Cysteinyl leukotrienes are involved in the pathogenesis of postinfectious cough and whooping cough (pertussis). We investigated the effectiveness of montelukast, a cysteinyl leukotriene receptor antagonist, in the treatment of postinfectious cough. METHODS: In this randomised, placebo-controlled trial, non-smoking adults aged 16-49 years with postinfectious cough of 2-8 weeks' duration were recruited from 25 general practices in England. Patients were tested for pertussis (oral fluid anti-pertussis toxin IgG) and randomly assigned (1:1) to montelukast 10 mg daily or image-matched placebo for 2 weeks. Patients chose whether to continue study drug for another 2 weeks. The randomisation sequence was computer-generated and stratified by general practice. Patients, health-care professionals, and researchers were masked to treatment allocation. Effectiveness was assessed with the Leicester Cough Questionnaire to measure changes in cough-specific quality of life; the primary outcomes were changes in total score between baseline and two follow-up stages (2 weeks and 4 weeks). The primary analysis was by intention to treat with imputation by last observation carried forward. Recruitment closed on Sept 21, 2012, and follow-up has been completed. This trial is registered with EudraCT (2010-019647-19), UKCRN Portfolio (ID 8360), and ClinicalTrials.gov (NCT01279668). FINDINGS: From April 13, 2011, to Sept 21, 2012, we randomly assigned 276 patients to montelukast (n=137) or placebo (n=139). 70 (25%) patients had laboratory-confirmed pertussis. Improvements in cough-specific quality of life occurred in both groups after 2 weeks (montelukast: mean 2·7, 95% CI 2·2-3·3; placebo: 3·6, 2·9-4·3), but the difference between groups did not meet the minimum clinically important difference of 1·3 (mean difference -0·9, -1·7 to -0·04, p=0·04). This difference was not statistically significant in any sensitivity analyses. After 2 weeks, 192 of 259 participants from whom data were available elected to continue study drug (99 [77%] of 129 participants on montelukast; 93 [72%] of 130 on placebo). After 4 weeks, there were no significant between-group differences in cough-specific quality of life improvement (montelukast: 5·2, 4·5-5·9; placebo: 5·9, 5·1-6·7; mean difference -0·5, -1·5 to 0·6, p=0·38) or adverse event rates (21 (15%) of 137 patients on montelukast reported one or more adverse events; 31 (22%) of 139 on placebo; p=0·14). The most common adverse events reported were increased mucus production (montelukast, n=6; placebo, n=2), gastrointestinal disturbance (montelukast, n=3; placebo, n=5), and headache (montelukast, n=2; placebo, n=6). One serious adverse event was reported (placebo, n=1), which was unrelated to study drug (shortness of breath and throat tightness after severe coughing bouts). INTERPRETATION: Montelukast is not an effective treatment for postinfectious cough. However, the burden of postinfectious cough in primary care is high, making it an ideal setting for future antitussive treatment trials. FUNDING: National Institute for Health Research School for Primary Care Research, UK.